2019
DOI: 10.13057/biodiv/d200933
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation among the geographic population of Cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae) in Indonesia inferred from mitochondrial COI gene sequence

Abstract: Abstract. Nopriawansyah N, Rauf A, Kusumah YM, Nurmansyah A, Koesmaryono Y. 2019. Genetic variation among the geographic population of Cassava mealybug Phenacoccus manihoti (Hemiptera: Pseudococcidae) in Indonesia inferred from mitochondrial COI gene sequence. Biodiversitas 20: 2685-2692. Cassava mealybug, Phenacoccus manihoti Matile-Ferrero (Hemiptera: Pseudococcidae) is an invasive pest native to South America. Research was conducted with the objective to study genetic variation of cassava mealybug from diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Among 80 cassava field sites, the P. manihoti infestations were found in 77 sites (95%) distributed in Lampung, Banten, West Java, Central Java, East Java, West Nusa Tenggara, and East Nusa Tenggara. More recently, P. manihoti was reported being present in Bangka (Nopriawansyah et al 2019). Personal communication with other scientists (Hidrayani of Andalas University, West Sumatra and Adriani Ichsan of State University of Gorontalo, Gorontalo) suggested that P. manihoti has been found in West Sumatra as well as North Sulawesi.…”
Section: Distribution and Infestation Of P Manihotimentioning
confidence: 97%
“…Among 80 cassava field sites, the P. manihoti infestations were found in 77 sites (95%) distributed in Lampung, Banten, West Java, Central Java, East Java, West Nusa Tenggara, and East Nusa Tenggara. More recently, P. manihoti was reported being present in Bangka (Nopriawansyah et al 2019). Personal communication with other scientists (Hidrayani of Andalas University, West Sumatra and Adriani Ichsan of State University of Gorontalo, Gorontalo) suggested that P. manihoti has been found in West Sumatra as well as North Sulawesi.…”
Section: Distribution and Infestation Of P Manihotimentioning
confidence: 97%
“…Similar to Lepidotrigona, the genus Tetragonula showed a small variation in the genetic distance (0.01-0.08) (Table 5). The genetic distance can indicate how DNA transfers between populations (gene flow) and leads to microevolution (Nopriawansyah et al 2019).…”
Section: Molecular Identificationmentioning
confidence: 99%